Lipoxin-Induced Phenotypic Changes in CD115+LY6Chi Monocytes TAM Precursors Inhibits Tumor Development - de-Brito, Natália Mesquita; da-Costa, Hayandra Cunha; Simões, Rafael Loureiro; Barja-Fidalgo, Christina (Frontiers in Oncology, 2019)
Abstract: During tumor development, the spleen acts as an extra-medullar reservoir of LY6Chigh inflammatory monocytes, which can migrate towards tumor to differentiate into tumor-associated macrophage (TAMs), renewing the TAM population. In the tumor microenvironment, pro-inflammatory macrophages (M1) acquire anti-inflammatory and pro-tumor (M2) characteristics favoring tumor development. We previously demonstrated that lipoxins, a family of pro-resolving lipid mediators, restored in vitro the cytotoxic M1-like properties of TAMs. Objective: In this study, we have investigated in vivo the cellular mechanisms underlying the anti-tumor property of lipoxins. Methods: Fourteen days after inducing B16-F10 melanoma tumors, mice received one single dose of ATL-1 (1 µg/i.v.), a lipoxin A4 analogue. After further 7 days, blood and bone-marrow were collected, tumors and spleens were removed, and TAMs and blood monocytes were isolated. Results: While the population of LY6Chigh monocytes was increased in non-treated tumor-bearing mice, the treatment with ATL-1 diminished the population of LY6Chigh monocytes in spleen, blood and bone marrow, decreasing macrophage infiltration into the tumor and reducing the M2 markers expression on TAMs. Importantly, those effects were accompanied by an impairment of tumor growth and improved survival of tumor-bearing mice. The data evidence the anti-tumor mechanism of ATL-1, by decreasing the availability of TAM-precursor monocytes and changing TAMs profile in vivo, impairing tumor progression. ATL-1 may become a new tool in cancer control.